Controllable fabrication of urchin-like Co3O4 hollow spheres for high-performance supercapacitors and lithium-ion batteries. Issue 38 (1st September 2016) - Chen, Fashen; Liu, Xiaohe; Zhang, Zhian; Zhang, Ning; Pan, Anqiang; Liang, Shuquan; Ma, Renzhi
Abstract : Urchin-like cobalt oxide (Co3 O4 ) hollow spheres can be successfully prepared by thermal decomposition of cobalt carbonate hydroxide hydrate (Co(CO3 )0.5 (OH)·0.11H2 O) obtained by template-assisted hydrothermal synthesis. Abstract : Urchin-like cobalt oxide (Co3 O4 ) hollow spheres can be successfully prepared by thermal decomposition of cobalt carbonate hydroxide hydrate (Co(CO3 )0.5 (OH)·0.11H2 O) obtained by template-assisted hydrothermal synthesis. The morphology, crystal structure evolution and thermal decomposition behaviors of the as-prepared products have been carefully investigated. A plausible formation mechanism of the urchin-like Co3 O4 hollow spheres in the presence of hexadecyl trimethyl ammonium bromide (CTAB) as the surfactant template is proposed. The urchin-like Co3 O4 hollow spheres are further constructed as electrode materials for high-performance supercapacitors with a high specific capacitance of 460 F g −1 at a current density of 4 A g −1 and excellent cycling stability. Furthermore, as anode materials for lithium-ion batteries (LIBs), superior lithium storage performance of 1342.2 mA h g −1 (0.1 C) and 1122.7 mA h g −1 (0.2 C) can also be achieved. The excellent performances can be ascribed to the unique hierarchical urchin-like hollow structure of the electrode materials, which offers a large specific surface area, short electron and ion diffusion paths and high permeability while being directly in contact with the electrolyte. Moreover, the hollow structure with sufficient internal void spaces can self-accommodate volume change during electrochemical reactions, which improves the structural stability and integrity.